3D printing of β-TCP/Alginate Scaffolds for Bone Regeneration - Carlos, Gabriela Soares Diogo (2018)
The rise of bone defects in the last decades has become a worldwide problem. They can arise from several causes such as tumors, trauma, infection, nutrition and bone diseases. This may compromise the mechanical and biological functions of bone tissue. Autografts, allografts and xenografts are some attractive alternatives used for bone tissue regeneration, however, several factors such as high risk of infection, immunogenic response and lack of donor has limited their use. Tissue Engineering is an interdisciplinary area that combines biomaterials and bioactive molecules to promote the repair and regeneration of bone. Scaffolds are 3D matrices that act as temporary templates, allowing cell adhesion and proliferation providing mechanical support until new bone tissue formation. Rapid prototyping technologies allow the production of 3D structures with controlled architecture from models created by computer-aided design, through a layer-by-layer process. The present work describes the production and characterization of βeta-Tricalcium phosphate/Alginate 3D scaffolds. Higher concentrations of βeta-Tricalcium phosphate provide structures with better mechanical and biological properties.